Peningkatan prestasi siswa tentang senam lantai melalui penggabungan kekuatan dua orang penjaskes - Wiyono Wiyono (Patria Educational Journal (PEJ), 2023)
The aims of this research are: 1). Describe the effect of the learning method combining the strengths of two people on Physical Education learning outcomes. 2). Describe the understanding and mastery of the Physical Education subject after the application of the Strength of Two People Method. This study uses a class action research design. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. The conclusion from this research is that through the Power of Two Person Merging Method it can have a positive effect on the student learning process, and this learning model can be used as an alternative to Physical Education